Global perspectives of determinants influencing HPV vaccine introduction and scale-up in low- and middle-income countries. - Dominique Guillaume; Dur-E-Nayab Waheed; Meike Schleiff; Kirthini Kasi Muralidharan; Alex Vorsters; Rupali J Limaye (PLoS ONE)
Achieving WHO cervical cancer elimination goals will necessitate efforts to increase HPV vaccine access and coverage in low-and-middle-income countries (LMICs). Although LMICs account for the majority of cervical cancer cases globally, scale-up of HPV vaccine programs and progress toward coverage targets in LMICs has been largely insufficient. Understanding the barriers and facilitators that stakeholders face in the introduction and scale-up of HPV vaccination programs will be pivotal in ensuring that LMICs are equipped to optimize the implementation of HPV vaccination programs. This qualitative study interviewed 13 global stakeholders categorized as either academic partners or global immunization partners to ascertain perspectives regarding factors affecting the introduction and scale-up of HPV vaccination programs in LMICs. Global stakeholders were selected as their perspectives have not been as readily highlighted within the literature despite their key role in HPV vaccination programming. The results of this investigation identified upstream (e.g., financial considerations, vaccine prioritization, global supply, capacity and delivery, and vaccine accessibility, equity, and ethics) and downstream (e.g., vaccine acceptability and hesitancy, communications, advocacy, and social mobilization) determinants that impact program introduction and scale-up and confirmed that strong political commitment and governance are significant in garnering support for HPV vaccines. As LMICs introduce HPV vaccines into their national immunization programs and develop plans for scaling up vaccination efforts, strategic approaches to communications and advocacy will also be needed to successfully meet coverage targets.